South Sudan Governance Analysis : Building Sustainable Public Sector Capacity in a Challenging Context - World Bank (Washington, DC, 2017)
This report was developed in the first half of 2016, when the signing of the Agreement on the Resolution of Conflict in South Sudan (ARCISS) and subsequent establishment of the Transitional Government of National Unity (TGNU) presented a possible window of opportunity to restart and reset state-building effort, in particular, to initiate a more strategic approach to capacity building. From the government side, it was possible incentives will emerge to signal a break with the past by delivering services to citizens. In this context, the main objective of the note has been to contribute a stronger evidence base for renewed efforts at supporting capacity building. Despite the renewed deterioration since mid-2016, it is expected that many of the key challenges and tensions analyzed will remain important considerations when capacity building efforts are eventually renewed. South Sudan has faced renewed conflict and a deepening macro-fiscal crisis. Shortly after the formation of the TGNU in late May 2016, fighting broke out in Juba and the security situation in the rest of the country has subsequently deteriorated. This note mainly covers the period until June 2016, as a contribution to providing a more nuanced understanding of efforts at capacity building in South Sudan. This note is primarily concerned with capacity in the civilian public service in South Sudan, and its ability to deliver public services. The note explores cross-cutting issues and challenges related to developing a capable and effective civil service and drills down into two specific areas: public financial management (PFM) and the public health sector. The report combines an analysis of the opportunities and constraints created by the evolving country context; cross-cutting factors which have shaped core public administration functions across sectors since 2005; and analysis of capacity in two selected state functions PFM and health care. The report is organized as follows: chapter one presents purpose, scope, and approach. Chapter two covers the conceptual underpinnings of the paper. Chapter three provides a cross-cutting perspective on capacity-building efforts in South Sudan, providing an overview of public sector as a tool for the management of political support, as well as the evolution of aid architecture. Chapter four covers PFM in South Sudan and chapter five addresses the health sector. Chapter six reviews key findings and emerging lessons and concludes with recommendations and options for improving monitoring of capacity-building efforts going forward.